Strategi Pemasaran Produk Tabungan Batara iB Dengan Akad Wadiah Pada Bank BTN Syariah KCPS Pasuruan - Loviana, Erisa; Bakhri, Saiful (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
This research is entitled marketing strategy for Batara iB Akad Wadiah savings products regarding customer interest in BTN Syariah bank. Strategy is a fundamental tool that is planned to achieve company goals by developing sustainable competitive advantages through the markets entered and marketing programs used to serve these target markets. In its activities, Bank BTN Syariah needs to market Batara iB products with the right strategy so that it can fulfill the wants and needs of the community or customers well. The formulation of the problem in this research is how the marketing strategy and constraints and efforts of the Batara iB Bank BTN Syariah Savings Product on Batara iB savings are to use the concept of promotional marketing strategies, namely individual or institutional promotional strategies, promotional strategies through the media, promotional strategies through financing and the obstacles faced in the form of competition from other products, lack of public understanding and trust regarding savings in Sharia Banks and lack of distribution in offices and machines. Apart from that, there are also efforts to overcome obstacles, namely, to prioritize savings products by providing an understanding of the benefits that savings have at the relevant banks, and also the provision of ATMs which should be more widely distributed to attract public interest.